2019
DOI: 10.1021/acs.est.9b01732
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Polycyclic Aromatic Hydrocarbon Oxidation Products in α-Pinene Secondary Organic Aerosol Particles Formed through Ozonolysis

Abstract: Accurate long-range atmospheric transport (LRAT) modeling of polycyclic aromatic hydrocarbons (PAHs) and PAH oxidation products (PAH-OPs) in secondary organic aerosol (SOA) particles relies on the known chemical composition of the particles. Four PAHs, phenanthrene (PHE), dibenzothiophene (DBT), pyrene (PYR), and benz(a)anthracene (BaA), were studied individually to identify and quantify PAH-OPs produced and incorporated into SOA particles formed by ozonolysis of α-pinene in the presence of PAH vapor. SOA part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The primary BBOA‐1 (O/C of 0.26 and 0.21 at HK and PF, respectively) contained abundant signals associated with PAH compounds at m/z 115, 128, 152, 165, 189, 202, 239 and 252 (Figure S9 in Supporting Information ), which are mostly associated with incomplete combustion of fuels containing organic material such as coal (Chen et al., 2005), wood (Simoneit, 2002), crop‐residue (Lu et al., 2009), fossil fuels (Fujita et al., 2007) and animal dung (Gadi et al., 2012). The PAH signals decreased both in intensity and number of m/z 's present (115, 152 and 165) in the partially oxidized BBOA‐2 (O/C of 0.28 and 0.34), and almost negligible in the most oxidized BBOA‐3 (O/C of 0.71 and 0.46) which could be because of its incorporation and assistance in the SOA formation processes as has been previously observed (Kramer et al., 2019; Zelenyuk et al., 2017). This was also supported by the presence of small amounts of PAH signals in the highly oxidized low‐volatile OOA (at m/z 115, 128, 152, 165 and 178) with an O/C of 0.77 and 1.03 at HK and PF, respectively, NO 3 ‐OA (at m/z 115, 152, 165 and 202) with an O/C of 0.9 and 1.0, and SO 4 ‐OA (at m/z 115 and 165) with an O/C of 1.2 and 1.1 (Figure S9 in Supporting Information ).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The primary BBOA‐1 (O/C of 0.26 and 0.21 at HK and PF, respectively) contained abundant signals associated with PAH compounds at m/z 115, 128, 152, 165, 189, 202, 239 and 252 (Figure S9 in Supporting Information ), which are mostly associated with incomplete combustion of fuels containing organic material such as coal (Chen et al., 2005), wood (Simoneit, 2002), crop‐residue (Lu et al., 2009), fossil fuels (Fujita et al., 2007) and animal dung (Gadi et al., 2012). The PAH signals decreased both in intensity and number of m/z 's present (115, 152 and 165) in the partially oxidized BBOA‐2 (O/C of 0.28 and 0.34), and almost negligible in the most oxidized BBOA‐3 (O/C of 0.71 and 0.46) which could be because of its incorporation and assistance in the SOA formation processes as has been previously observed (Kramer et al., 2019; Zelenyuk et al., 2017). This was also supported by the presence of small amounts of PAH signals in the highly oxidized low‐volatile OOA (at m/z 115, 128, 152, 165 and 178) with an O/C of 0.77 and 1.03 at HK and PF, respectively, NO 3 ‐OA (at m/z 115, 152, 165 and 202) with an O/C of 0.9 and 1.0, and SO 4 ‐OA (at m/z 115 and 165) with an O/C of 1.2 and 1.1 (Figure S9 in Supporting Information ).…”
Section: Resultssupporting
confidence: 68%
“…(2021) where dark oxidation of fresh BB emissions in the presence of NO x and O 3 resulted in high yields of NO 3 and NO 3 ‐related OA, and field studies related to the nighttime transformation of BB plumes (Decker et al., 2019). Further, the presence of high levels of VOCs (equivalent to the AGB period) related to BB (toluene and furan; Figure S15 in Supporting Information ) and PAH signals in NO 3 ‐OA mass spectra (Figure S9 in Supporting Information ), which could be due to adsorption onto SOA particles during their formation (Kramer et al., 2019; Zelenyuk et al., 2017), points toward BB as the major source of SOA. High levels of furans and phenols have been previously observed in Delhi during the late winter season in earlier studies (Wang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the years since, a number of other classes of mutagenic metabolites ( Figure 1 ), such as quinones and diols, have since been detected in PM 80 , 81 , 92 and in controlled laboratory studies involving the oxidation of PAHs. 44 , 79 , 82 Recently, it was even shown that B[a]P-diol-epoxides (a class of compounds that includes BDPE, a potent carcinogen) were formed by the atmospheric oxidation of B[a]P. 40 Such studies affirm that atmospheric oxidation ( Figure 2 ) can form species that are the same as (or regioisomers of) those generated throughout the metabolic activation chain ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 93%
“… 99 have recently shown that the position of OH groups on naphthalene derivatives determined bioactivity and, in some cases, which tissue was targeted. Therefore, comprehensive studies of PAH oxidation products 79 , 80 paired with toxicity studies of these products 99 and product mixtures 100 are needed to provide information on the toxicity of the full distribution of oxidized PAHs formed in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation